Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/2080854
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Node Localization Approach with RSSI for Randomly Deployed Wireless Sensor Networks

Abstract: An efficient path planning approach in mobile beacon localization for the randomly deployed wireless sensor nodes is proposed in this paper. Firstly, in order to improve localization accuracy, the weighting function based on the distance between nodes is constructed. Moreover, an iterative multilateration algorithm is also presented to avoid decreasing the localization accuracy. Furthermore, a path planning algorithm based on grid scan which can traverse entirely in sensor field is described. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Depending on the technique used to estimate distances in a localization algorithm, the localization algorithms can be divided into two main groups [18]: Range-based localization algorithm and Rangefree localization algorithms. Range-Based localization algorithms [19] are those algorithms that use distance or angle measurements techniques such as RSSI [19], [23], Time Difference of Arrival (TDoA) [11], Time of Arrival (ToA) [22], and Angle of Arrival (AoA) [14]. While range-free localization algorithms use connectivity information [7], i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Depending on the technique used to estimate distances in a localization algorithm, the localization algorithms can be divided into two main groups [18]: Range-based localization algorithm and Rangefree localization algorithms. Range-Based localization algorithms [19] are those algorithms that use distance or angle measurements techniques such as RSSI [19], [23], Time Difference of Arrival (TDoA) [11], Time of Arrival (ToA) [22], and Angle of Arrival (AoA) [14]. While range-free localization algorithms use connectivity information [7], i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Advanced trilateration localization algorithms were proposed by Yan et al [19] and Monta et al [20], both offering improvements on distance estimation. Liu and Cai [21] and Zhang et al [22] also reported enhanced trilateration localization methods, with the latter proposing an iterative trilateration approach to maintain localization accuracy. A novel improvement for the trilateration technique using fuzzy logic was developed by El Samadony et al [23], adding power level as an additional parameter for distance estimation between anchors and nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Iterative multi lateralization technique and algorithm start conditions are also provided to avoid loss of localization accuracy during the iterative phase, according to the study. X. Zhang, et al [26] suggested a numerous localization technique using the TDOA has provided information for UWB MIMO cognitive radar. If there are many targets, different correlation peaks show the TDAs of those targets.…”
Section: Literature Surveymentioning
confidence: 99%